MEDIA “FRIDGE MAGNET SERIES” MENINGKATKAN PENGETAHUAN DAN SIKAP HIGIENE SANITASI IBU RUMAH TANGGA - Mustoviani, Gita; Nuzrina, Rachmanida (JURNAL RISET GIZI, 2021)
Background: Most of housewives do not understand food sanitation hygiene yet. It caused by lack of education on households food sanitation hygiene. The importance of food sanitation hygiene education to prevent foodborne diseases. One of the educational media which can used is the educational fridge magnet series media.Objective: To assess the impacts of educational fridge magnet series media towards knowledge and attitude improvement related with housewives' hygiene food sanitation.Methods: A quasi-experimental study with a non-equivalent control group pretest-posttest design. Subjects were devided into two gropus, 31 subjects from the intervention group and 30 subjects in control group. In the intervention group, subjects were given educational fridge magnet series media and lecturing session, while the control group were given lecturing-session only. Data analysis were used Paired Sample T-test, Wilcoxon, Independent Sample T-test, and Mann-Whitney.Results: There were significant differences on housewives' knowledge before and after education in the intervention group (p=0,000) and control (p=0,015). There were differences on attitudes before and after education in the intervention (p=0,000) and control (p=0,022). Knowledge score were increased by 20,00 and attitude score by 9,59 in the intervention group after education with fridge magnet series media. In the control group, the knowledge score after education were increased from 3,66 only. Meanwhile, the attitude score showed decrease by 1,98. After education, there were differences in knowledge (p=0.000) and attitudes (p= 0,000) between the two groups.Conclusion: Educational fridge magnet series media has impacts on increasing housewives' knowledge and attitudes related food sanitation hygiene. Interventions with educational media more effective than lecturing-session.